Gut microbiome and mycobiome in inflammatory bowel disease patients with Clostridioides difficile infection - Yu, Si; Ge, Xiaomeng; Xu, Hui; Tan, Bei; Tian, Bowen; Shi, Yujie; Dai, Yimin; Li, Yue; Hu, Songnian; Qian, Jiaming (Frontiers in Cellular and Infection Microbiology, 2023)
Background Clostridium difficile infection (CDI) is common in patients with inflammatory bowel disease (IBD) and has been reported as a risk factor for poor outcome. However, gut microbiome and mycobiome of IBD patients with CDI have been barely investigated. This study aimed to assess the gut microbiome and mycobiome in IBD patients with CDI. Methods We collected fecal samples from patients with active IBD and concomitant CDI (IBD-CDI group, n=25), patients with active IBD and no CDI (IBD-only group, n=51), and healthy subjects (HC, n=40). Patients’ characteristics including demographic data, disease severity, and medication history were collected. Metagenomic sequencing, taxonomic and functional analysis were carried out in the samples. Results We found that the bacterial alpha diversity of the IBD-CDI group was decreased. The bacterial and fungal beta diversity variations between IBD patients and HC were significant, regardless of CDI status. But the IBD-CDI group did not significantly cluster separately from the IBD-only group. Several bacterial taxa, including Enterococcus faecium, Ruminococcus gnavus, and Clostridium innocuum were overrepresented in the IBD-CDI group. Furthermore, IBD patients with CDI were distinguished by several fungal taxa, including overrepresentation of Saccharomyces cerevisiae. We also identified functional differences in IBD patients with CDI include enrichment of peptidoglycan biosynthesis. The network analysis indicated specific interactions between microbial markers in IBD-CDI patients. Conclusion IBD patients with CDI had pronounced microbial dysbiosis. Gut micro-ecological changes in IBD patients with CDI might provide insight into the pathological process and potential strategies for diagnosis and treatment in this subset of patients.